Kenali Isi Piringku Bagi Penderita Hipertensi - Rahmawati, Ika; Jayanti , Riski; Tusiyani, Tusiyani; Astuti , Uci Widi; Nisa , Yati Sholehatun; Handayani, Tita Septi (Jurnal Karya Nyata Pengabdian, 2024)
Hypertension is a non-communicable disease that is often encountered and experienced by the general public in Indonesia and even in the world. Not a few suffer from this disease with or without symptoms causing complications and even death, hypertension is also a major risk factor that causes death throughout the world (Husen et al., 2022). Data from the World Health Organization (WHO) shows the prevalence of hypertension sufferers who have been diagnosed in 32 countries, namely 36.7% men and 50.8% women, 19.1% men and 33.4% men who are undergoing treatment for hypertension. %, and those whose hypertension is controlled are 5.5% men and 11.7% women (WHO, 2021). The prevalence of hypertension in Indonesia based on a doctor's diagnosis or taking hypertension medication in the population aged >18 years is 658,201 people (Indonesian Ministry of Health, 2019 ). Based on data from the profile of the South Sumatra Health Service in 2022, there were 1,497,736 (South Sumatra Health Office 2022). Hypertension is number 1 of the 10 biggest diseases, based on the total number of patient visits at the Megang Lubuk Linggau Timur II Community Health Center, especially in RT 01 Batu Urip Village in 2023 with a total of 50 patients (Megang Health Center, 2023).